Carbon Footprint of Food Consumption by Cats and Dogs in Brazil - Boaventura, Júlia Fernandes; Gameiro, Augusto Hauber (Journal of Agricultural Studies, 2025)
Greenhouse gas emissions increase every year and their effects on a global scale are increasingly greater and more noticeable. Consequently, there is also a growing concern related to environmental issues. Among the many factors involved in raising dogs and cats, their diet is one of the most important. It requires a large amount of food inputs, which despite increasing every year and being responsible for a portion of current greenhouse gas emissions, still receive little attention from the scientific community and the media. To verify the potential impacts of raising companion animals in Brazil, this work estimated the carbon footprint generated by feeding dogs and cats in the country through a mathematical model. In this model, an average Brazilian dogs and cats is considered, as well as a standard dog and cat food, and the annual consumption of each ingredient present in the food. The results showed an estimated carbon footprint per capita of 334.06 kg CO2-eq/year for dogs and 147.73 kg CO2-eq/year for cats, totaling an estimate of 18.67 x 109 kg CO2-eq/year for the Brazilian population of dogs and 3.78 x 109 kg CO2-eq/year for the Brazilian population of cats.